2003
DOI: 10.2169/internalmedicine.42.793
|View full text |Cite
|
Sign up to set email alerts
|

Ticlopidine Alone Versus Ticlopidine Plus Aspirin for Preventing Recurrent Stroke

Abstract: Objective To compare the efficacy and safety of two antiplatelet regimens, ticlopidine alone (200 mg daily) and ticlopidine (100 mg daily) plus aspirin (81 mg daily), in patients with ischemic stroke from the Tokai district of Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A systematic review provides therefore stronger evidence. Sorensen et al 50 Bousser et al 6 Fields et al 22 Helmers et al 28 Boysen et al 7 Gent et al (CAPRIE study) 24 Lowenthal et al 34 Norrving et al 40 Farrel et al 21 Gent et al (CATS study) 25 Diener et al (ESPS study) 17 MacMahon et al 35 Gates et al 23 Matias-Guiu et al 38 Ito et al 30 Diener et al (MATCH study) 18 Toole et al 51 Collins et al 14 Chimowitz et al 12 Ovbiagele et al 42 Boysen et al (ExSTROKE study) 8 Figure S3. Forest plot of the meta-analysis of the risk of MI after TIA/IS in hospital-based studies.…”
Section: -6a Was the Follow Up Of Subjects Complete Enough?mentioning
confidence: 99%
“…A systematic review provides therefore stronger evidence. Sorensen et al 50 Bousser et al 6 Fields et al 22 Helmers et al 28 Boysen et al 7 Gent et al (CAPRIE study) 24 Lowenthal et al 34 Norrving et al 40 Farrel et al 21 Gent et al (CATS study) 25 Diener et al (ESPS study) 17 MacMahon et al 35 Gates et al 23 Matias-Guiu et al 38 Ito et al 30 Diener et al (MATCH study) 18 Toole et al 51 Collins et al 14 Chimowitz et al 12 Ovbiagele et al 42 Boysen et al (ExSTROKE study) 8 Figure S3. Forest plot of the meta-analysis of the risk of MI after TIA/IS in hospital-based studies.…”
Section: -6a Was the Follow Up Of Subjects Complete Enough?mentioning
confidence: 99%
“…Fifty‐five articles were reviewed by full text for details, and 31 of those were excluded. Finally, a total of 24 RCTs with 85 667 patients were included in the present network meta‐analysis . Tables and summarize the characteristics of the 24 included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Tables and summarize the characteristics of the 24 included trials. The following antiplatelet therapies were tested in the trials: cilostazol versus aspirin (3 trials with 3459 patients), clopidogrel versus aspirin (1 trial with 6431 patients), dipyridamole versus aspirin (1 trial with 3303 patients), sarpogrelate versus aspirin (1 trial with 1499 patients), terutroban versus aspirin (1 trial with 19 100 patients), ticlopidine versus aspirin (4 trials with 5488 patients), ticlopidine versus clopidogrel (1 trial with 1151 patients), triflusal versus aspirin (2 trials with 2536 patients), aspirin plus clopidogrel versus aspirin (2 trials with 7340 patients), aspirin plus clopidogrel versus clopidogrel (1 trial with 7599 patients), aspirin plus dipyridamole versus aspirin (5 trials with 8622 patients), aspirin plus dipyridamole versus clopidogrel (1 trial with 20 332 patients), aspirin plus dipyridamole versus dipyridamole (2 trials with 3490 patients), and aspirin plus ticlopidine versus ticlopidine (1 trial with 270 patients) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This recommendation was supported by four citations [1][2][3][4] , which included a systematic review and meta-analysis; this was used as the starting point for our PubMed search. 4 The meta-analysis focused on seven randomized, controlled studies 1,[5][6][7][8][9][10] ; that included patients with recent history of stroke or transient ischemic attack (TIA); and that compared DPT versus monotherapy. The meta-analysis indicated that DPT was superior to aspirin alone, but not to clopidogrel alone, and that dual anti-platelet therapy was more harmful than clopidogrel.…”
Section: Related Literaturementioning
confidence: 99%